SUSTAINABLE ENERGY MANAGEMENT STRATEGIES IN HOSPITALS: EXAMINATION AND ANALYSIS - Sorooshian, Shahryar; Omid Jabbari; Ardalan Feili (Homes Journal: Hospital Management Studies Journal, 2024)
Background: Sustainable development is often defined as the process of change by which the current needs of society are without hindering the capacity of future generations to meet their needs. Hospitals and medical centers are among the most vital organizations in any society and are among the largest consumers of water and energy and producers of waste. Objective: The purpose of this study was to identify and rank sustainable energy management strategies in Farabi Hospital. Method: The present study is applied in terms of purpose and descriptive in terms of methodology. For collecting data, a researcher-made questionnaire based on multi-attribute decision-making methods used in this study (test and evaluation decision method, network analysis method, simple weight total, and Linmap) was used, which were completed by ten experts familiar with the topic of sustainable energy management with at least ten years of experience in Farabi Hospital in Bastak city in Hormozgan province. Result: The results of data analysis indicated that reduction of fossil energy consumption, waste recycling, and renewable energy are respectively the most significant criteria for sustainable energy management in hospitals while employing equipment for reducing water consumption, installing automatic doors, and utilization of rainwater collection system are respectively the most important criteria for optimized, sustainable development Conclusion: According to the study results, the hospital managers are required to adopt combined solutions for energy management in the water and electricity sectors to focus on reducing energy waste and the use of new energy sources such as solar and rainwater.